Radio morphology of southern narrow-line Seyfert 1 galaxies with Very Large Array observations. Issue 1 (24th August 2020) - Chen, S; Järvelä, E; Crepaldi, L; Zhou, M; Ciroi, S; Berton, M; Kharb, P; Foschini, L; Gu, M; La Mura, G; Vietri, A
ABSTRACT: We present the results of new radio observations carried out with the Karl G. Jansky Very Large Array C-configuration at 5.5 GHz for a sample of southern narrow-line Seyfert 1 galaxies (NLS1s). This work increases the number of known radio-detected NLS1s in the Southern hemisphere, and confirms that the radio emission of NLS1s is mainly concentrated in a central region at kpc-scale and only a few sources show diffuse emission. In radio-quiet NLS1s, the radio luminosity tends to be higher in steep-spectrum sources and be lower in flat-spectrum sources, which is opposite to radio-loud NLS1s. This may be because the radio emission of steep NLS1s is dominated by misaligned jets, active galactic nucleus driven outflows, or star formation superposing on a compact core. Instead the radio emission of flat NLS1s may be produced by a central core that has not yet developed radio jets and outflows. We discover new NLS1s harbouring kpc-scale radio jets and confirm that a powerful jet does not require a large-mass black hole to be generated. We also find sources dominated by star formation. These NLS1s could be new candidates in investigating the radio emission of different mechanisms.